Evaluasi Website E-Wartawan Menggunakan ISO 27001 dalam Meningkatkan Keamanan Informasi di Kantor Diskominfotik - Rapiana Rapiana; Mansur Mansur (Lembaga Pengembangan Kinerja Dosen, 2025)
Information security is a crucial aspect in managing digital government systems, particularly for services that store sensitive data. The e-Journalist website managed by the Bengkalis Regency Communications and Information Technology Office Discominfotik serves as a communication medium between the government and the press, requiring optimal information security to prevent data leaks or misuse. This study aims to evaluate the level of information security in the e-Journalist system using the ISO/IEC 27001 standard. The evaluation was conducted based on the seven main clauses of ISO 27001: Organizational Context, Leadership, Planning, Support, Operation, Evaluation, and Improvement, and used the SSE-CMM maturity level measurement approach. The research method used was a quantitative approach through questionnaire distribution and direct observation. The evaluation results showed an average maturity level score of 2.39, which falls into the Repeatable but Intuitive category, meaning that information security processes have been implemented repeatedly but have not been formally documented.